The COVID-19 Epidemic: Management and Outcomes of Hemodialysis and Peritoneal Dialysis Patients in Stockholm, Sweden - Jessica Smolander; Annette Bruchfeld (Karger Publishers, 2021)
Background: The COVID-19 outbreak has been associated with a high morbidity, mortality, and a risk of long-term sequelae, and patients with severe COVID-19 are at increased risk of acute kidney injury. CKD patients are at high risk of being exposed to COVID-19 and suffer complications and poor outcome. In Sweden, mitigation strategies did not include lockdown. During March-April of 2020, wide-spread infection occurred in Stockholm. Methods: Management and outcomes in forty hemodialysis (HD) patients and 4 peritoneal dialysis (PD) patients, with symptomatic COVID-19 in greater Stockholm during March and April of 2020 are reported. Results: Twenty-four HD patients (60%) required medical care and hospitalization, whereas 16 patients (40%) were treated at home. Nine patients died (mortality rate of 22.5%), of whom 8 were men. The median age in non-survivors (78 years) was significantly higher than in survivors (p = 0.003). The median time in dialysis (11.5 years) was also significantly longer in non-survivors (p = 0.01). C-reactive protein (CRP) at diagnosis in 7 of non-survivors (median 213 mg/L, range 86-329 mg/L) was significantly higher than the CRP in 25 survivors (median 87 mg/L, range 1-328 mg/L) (p = 0.0003). Maximum CRP also indicated poorer outcome among hospitalized patients (p = 0.0004). The gender imbalance was striking with only men dying apart from 1 elderly woman. Only 4 PD patients were hospitalized with symptomatic COVID-19. One patient died, 2 were discharged, and 1 was treated at the intensive care unit and survived. Conclusion: HD patients >70 years were reported with longer dialysis vintage, higher CRP, and males were at an increased risk of dying from COVID-19, whereas those <70 years seemed to have a milder disease. Mitigation strategies to reduce rates of infection in high-risk populations remain essential. Follow-up focusing on long-term prognosis for extrapulmonary manifestations is likely to be important also in dialysis patients.